Practicing Good CYBER HYGIENE. - BROYLES, DAVID (Public Management (00333611), 2020)
The article discusses that COVID-19 pandemic has re-emphasized the importance of personal hygiene. It mentions the formal calculation of attack surface takes a complete accounting of a computer networks resources and computes the sum of their contributions to the potential for damage; and also mentions some local governments and other organizations have rapidly deployed new network infrastructure in order to accommodate the surge in demand for teleworking.